Som - do lúdico ao aprendizado concreto com educandos do 4º ano do ensino fundamental - Dopfer, Edilberto Erasmo (2019)
The Science teaching in the elementary school is the base to graduate new searchers. By this work it is aimed in an edutainment, through it the children can build their own experiment. By simple experiments and with low cost, it allows the children have contact with these experiments so they get their own hypothesis about what it is happening and formulate theories about them, moreover they can realize the scientific knowledge is part of historical construction so it is possible to star the Physical teaching since the first years of Elementary School. The educational product developed during this work refers to the sound study to 4thgrade of elementary school. During the work application it was aimed the children’s comprehension of knowledge about the sound propagation in different environments, how it propagates and how fast this propagation is in each material environment, moreover the quality of sound as the loud, intensity and the timbre. It shows the noise pollution theme and its damages that causes in the human health, besides searching the comprehension of how the human ear works and reacts to the sounds it hears. The experiments are really simple and of low cost, using recyclable materials, as used plastic bags, jars and cans which would go to trash, so it can be used in public schools. There is also some experiments that students can play with them during the class, for example cordless phone and drum. Through this work we tried to awake in the children the curiosity of scientific knowledge, furthermore educating them enough in order to interact with situations they face day by day and try them with other materials and other phenomenon which are related to the understood studies during the activities done. As a result it is possible to relate the children interact in a spontaneous way, answering questions, building the experiments, handling, raising hypothesis and theories about how each phenomenon happens consequently the class was engaged and with a good harnessing. This educational product was based in the Piaget theory about the learning stages, more specifically the Concrete Operational.